2014
DOI: 10.1523/jneurosci.4447-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Switch in GABA Polarity Is Delayed in Fragile X Mice

Abstract: Delays in synaptic and neuronal development in the cortex are key hallmarks of fragile X syndrome, a prevalent neurodevelopmental disorder that causes intellectual disability and sensory deficits and is the most common known cause of autism. Previous studies have demonstrated that the normal progression of plasticity and synaptic refinement during the critical period is altered in the cortex of fragile X mice. Although the disruptions in excitatory synapses are well documented in fragile X, there is less known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
190
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(205 citation statements)
references
References 22 publications
15
190
0
Order By: Relevance
“…As a result, the lack of KCC2 in Rett neurons causes brain development to stall. Consistent with our study in human Rett neurons, a delayed GABA functional switch has also been reported in mouse models of autism and fragile X syndrome (47,48). Interestingly, we demonstrate that elevating KCC2 level can reverse the functional deficits caused by MeCP2 deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the lack of KCC2 in Rett neurons causes brain development to stall. Consistent with our study in human Rett neurons, a delayed GABA functional switch has also been reported in mouse models of autism and fragile X syndrome (47,48). Interestingly, we demonstrate that elevating KCC2 level can reverse the functional deficits caused by MeCP2 deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…A developmental shift in the expression of these proteins toward SLC12A5 regulates the transition of GABAergic transmission from depolarizing to hyperpolarizing. The diuretic NKCC1 inhibitor bumetanide has been proposed as a potential therapeutic in FXS and autism (56), and our data corroborate recent work suggesting that FXS may indeed involve an improper balance of SLC12A2 and SLC12A5 (10). Interestingly, at P45, both proteins were comparably expressed in WT and KO synapses, suggesting that the ratio imbalance evident in young cortex may continue into adulthood even as absolute levels of each decrease.…”
Section: Discussionsupporting
confidence: 89%
“…Substantial evidence indicates that FMRP is particularly critical as a suppressor of activity-dependent mRNA translation at glutamatergic synapses (6,7) and that loss of this function results in abnormalities in dendritic spine shape and several forms of long-term synaptic plasticity (8,9). In addition, significant changes have been described regarding the structure and/or function of other synaptic systems, including GABAergic and endocannabinoid synapses (10,11). Loss of FMRP expression has been recently linked to abnormalities in adult neurogenesis, migration, neural differentiation, and cortical maturation (12).…”
mentioning
confidence: 99%
“…(21,22). Increased intracellular chloride concentration and a change in the postsynaptic impact of GABAergic synapses have been demonstrated during development in mouse models of ASD, including fragile-X syndrome (23,24). Indirect evidence also points to this mechanism affecting RTT: Lower levels of KCC2 relative to NKCC1 have been found by immunoblot analysis of cerebrospinal fluid samples in patients with RTT (25); depolarizing GABAergic synapses in development follow from down-regulation of brain-derived neurotrophic factor (BDNF) (26), which is also an early consequence of MeCP2 deletion in mouse models (27); and insulin-like growth factor-1 (IGF1) treatment, which partially rescues behavioral and synaptic deficits in mutant mouse models of RTT (28,29), also activates KCC2 expression and restores the inhibitory action of GABAergic synapses in the hippocampus (30).…”
Section: Significancementioning
confidence: 99%